Colapso induzido pelo exercício em um Labrador Retriever - Basso, Roberta Martins [UNESP] (2014)
The exercise-induced collapse (EIC) is a hereditary disease characterized by muscle weakness, impaired locomotion and collapse after intense exercise. This autossomic recessive disorder affects mainly Labrador Retriever presenting the mutation c.767G>T in the dynamin 1 (DNM1) gene. The objective of this study is to report the first case of exercise-induced collapse in Labrador Retriever in Brazil. The molecular test detected the specific genetic mutation and confirmed the clinical diagnosis in a Labrador Retriever with clinical history of weakness and collapse after exercise. It is important to include this disease as part of the differential diagnosis of neuromuscular diseases in Labrador Retriever and use the molecular test to guide matings.